Sugar Transporter STP7 Specificity for l-Arabinose and d-Xylose Contrasts with the Typical Hexose Transporters STP8 and STP12. Issue 3 (8th January 2018) - Rottmann, Theresa; Klebl, Franz; Schneider, Sabine; Kischka, Dominik; Rüscher, David; Sauer, Norbert; Stadler, Ruth
Abstract : The hexose transporters STP8 and STP12 may contribute to the nutrition of reproductive tissues, whereas the pentose-specific STP7 might be involved in cell wall sugar recycling in Arabidopsis. Abstract: The controlled distribution of sugars between assimilate-exporting source tissues and sugar-consuming sink tissues is a key element for plant growth and development. Monosaccharide transporters of the SUGAR TRANSPORT PROTEIN (STP) family contribute to the uptake of sugars into sink cells. Here, we report on the characterization of STP7, STP8, and STP12, three previously uncharacterized members of this family in Arabidopsis ( Arabidopsis thaliana ). Heterologous expression in yeast ( Saccharomyces cerevisiae ) revealed that STP8 and STP12 catalyze the high-affinity proton-dependent uptake of glucose and also accept galactose and mannose. STP12 additionally transports xylose. STP8 and STP12 are highly expressed in reproductive organs, where their protein products might contribute to sugar uptake into the pollen tube and the embryo sac. stp8.1 and stp12.1 T-DNA insertion lines developed normally, which may point toward functional redundancy with other STPs. In contrast to all other STPs, STP7 does not transport hexoses but is specific for the pentoses l -arabinose and d -xylose. STP7- promoter-reporter gene plants showed an expression of STP7 especially in tissues with high cell wall turnover, indicating that STP7 might contribute to the uptake and recycling of cell wall sugars. Uptake analyses with radioactive l -arabinose revealed that 11 other STPs are able to transport l -arabinose with high affinity. Hence, functional redundancy might explain the missing-mutant phenotype of two stp7 T-DNA insertion lines. Together, these data complete the characterization of the STP family and present the STPs as new l -arabinose transporters for potential biotechnological applications.